Plasma concentration guided dosing of drugs used for the treatment of childhood leukaemias: protocol for a systematic review - Dyk, Madelé van; Boylan, Chelsea; Michelet, Robin; McLaughlin, Anna Margarete; Kichenadasse, Ganessan; May, Nikki; Ziesenitz, Victoria C.; Anker, Johannes N. Van Den; Groenland, Stefanie L.; Huitema, Alwin D. R.; Steeghs, Neeltje; Mikus, Gerd; et al. (BMJ open, 2022)
Introduction Childhood leukaemia is the most common type of cancer in children and represents among 25% of the diagnoses in children <15 years old. Childhood survival rates have significantly improved within the last 40 years due to a rapid advancement in therapeutic interventions. However, in high-risk groups, survival rates remain poor. Pharmacokinetic (PK) data of cancer medications in children are limited and thus current dosing regimens are based on studies with small sample sizes. In adults, large variability in PK is observed and dose individualisation (plasma concentration guided dosing) has been associated with improved clinical outcomes; whether this is true for children is still unknown. This provides an opportunity to explore this strategy in children to potentially reduce toxicities and ensure optimal dosing. This paper will provide a protocol to systematically review studies that have used dose individualisation of drugs used in the treatment of childhood leukaemias. - Methods and analysis Systematic review methodology will be applied to identify, select and extract data from published plasma guided dosing studies conducted in a paediatric leukaemia cohort. Databases (eg, Ovid Embase, Ovid MEDLINE, Ovid Cochrane) and clinical trial registries (CENTRAL, ClinicalTrials.gov and ISRCTN) will be used to perform the systematic literature search (up until February 2021). Only full empirical studies will be included, with primary clinical outcomes (progression-free survival, toxicities, minimal residual disease status, complete cytogenetic response, partial cytogenetic response and major molecular response) being used to decide whether the study will be included. The quality of included studies will be undertaken, with a subgroup analysis where appropriate. - Ethics and dissemination This systematic review will not require ethics approval as there will not be collection of primary data. Findings of this review will be made available through publications in peer-reviewed journals and conference presentations. Gaps will be identified in current literature to inform future-related research. - PROSPERO registration number CRD42021225045.